2018
DOI: 10.1111/jdv.15035
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical enthesopathy of extensor digitorum tendon is highly prevalent and associated with clinical and ultrasound alterations of the adjacent fingernails in patients with psoriatic disease

Abstract: Enthesopathy abnormalities can be detected by US in patients with psoriasis without musculoskeletal complaints frequently. There is a close relationship between subclinical enthesopathy of the extensor digitorum tendon and the presence of nail alterations. Further studies are required to research what implications have the presence of these ungual alterations measured by US, and how it affects later development of a PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 25 publications
0
22
1
Order By: Relevance
“…Even though the majority of studies have reported increased PD signal in the NB and NM of psoriatic patients [11,13,14,32,36,40], capillaroscopic evaluation of the proximal nailfold of these patients has shown decreased number and diameter of capillaries and increased vessel tortuosity [41,42]. In our study, the grade of NMPD signal and PD assessed in the NB and NM together failed to reveal differences between groups and the NBPD signal was more frequently absent in the PsA group.…”
Section: Discussioncontrasting
confidence: 72%
“…Even though the majority of studies have reported increased PD signal in the NB and NM of psoriatic patients [11,13,14,32,36,40], capillaroscopic evaluation of the proximal nailfold of these patients has shown decreased number and diameter of capillaries and increased vessel tortuosity [41,42]. In our study, the grade of NMPD signal and PD assessed in the NB and NM together failed to reveal differences between groups and the NBPD signal was more frequently absent in the PsA group.…”
Section: Discussioncontrasting
confidence: 72%
“…This is the first study, to our knowledge, that has assessed the relationship between nail disease and systemic peripheral enthesitis in established PsA. A previous study in psoriasis and pre-articular disease did not find a significant correlation between DIP enthesitis and Achilles tendon enthesitis [ 13 ]. In this study, we attempted to assess enthesitis both peripherally, at multiple sites, and at all fingers.…”
Section: Discussionmentioning
confidence: 89%
“…Development of NP may be the first sign of joint disease resulting from subclinical enthesitis in the closely anatomically associated entheses of the DIP extensor tendons(Figures 1, 4) (18,(53)(54)(55). This hypothesis is supported by results from several recent imaging studies showing that changes in the DIP joint capsule are closely linked to histologic nail changes and diffuse inflammatory responses extending from the enthesis to the nail (10,15,16,56,57). Specifically, patients with psoriasis with nail involvement have higher enthesopathy scores on ultrasound than patients without nail disease, as a result of entheseal thickening of the extensor tendon (16,56,57).…”
mentioning
confidence: 69%
“…This hypothesis is supported by results from several recent imaging studies showing that changes in the DIP joint capsule are closely linked to histologic nail changes and diffuse inflammatory responses extending from the enthesis to the nail (10,15,16,56,57). Specifically, patients with psoriasis with nail involvement have higher enthesopathy scores on ultrasound than patients without nail disease, as a result of entheseal thickening of the extensor tendon (16,56,57). Several studies have shown positive correlations between NAPSI scores and ultrasound evidence of enthesopathy (56,58).…”
mentioning
confidence: 70%